To calculate: The solution for the system of provided equations:

kolonelyf4 2021-11-17 Answered
To calculate: The solution for the system of provided equations:
5a2b+3c=10
3a+b2c=7
a+4b4c=3
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Melinda Olson
Answered 2021-11-18 Author has 20 answers
(A) 5a2b+3c=10
(B) 3a+b2c=7
(C) a+4b4c 3
Consider (A) or (B):
(A) 5a2b+3c=10
(B) 3a+b2c=7
Multiply (B) with 2:
(A) 5a2b+3c=10
2 (B) - 6a + 2b - 4c = -14
Now, add (A) and (B):
(D) ac=4
Consider (A) and (C):
(A) 5a2b+3c=10
(C) a+4b4c=3
Multiply (A) with 2:
2 (A) 10a - 4b + 6c = 20
(C) a+4b4c=3
Add both the above equastion:
(E) 11a+2c=17
Now consider (D) and (E):
(D) ac=4
(E) 11a+2c=17
Multipy (D) with 2:
2 (D) - 2a - 2c = -8
(E) 11a+2c=17
Now, add both the equastions and solve for a:
9a=9
(dividing both sides by 9)
a=1
Substitute 1 for a in (D):
(1)c=4
Adding 1 to both sides and then dividing by -1,
c=3
c=3
Substitude 3 for c and 1 for a in (A) and solve for b:
5(1)2b+3(3)=10
2b+14=10
Substracting 14 from both sides and then dividing by -2,
2b=4
b=2
2b=4
b=2
So, the values obtained are a=1, b=2 and c=3. Substitute thease values
in each of the provided equations to verify:
First Equation: 5(1)2(2)+3(3) 10
54+9 10
10 10
The result is true.
Second Equation:
-3 (1) + (2) - 2(3) -7
-3 + 2 -6 -7
-7 -7
The result is true.
Third Equation:
(1) + 4 (2) - 4(3) -3
1 + 8 - 12 -3
-3 -3
The result is true.
5a - 2b + 3c = 10
Therefore, the solution of the system of equations 3a+b2c=7 is
a+4b4c=3
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Relevant Questions

asked 2021-09-27
Describe the strategy you would use to solve log6xlog64+log68.
a. Use the product rule to turn the right side of the equation into a single logarithm. Recognize that the resulting value is equal to x.
b. Express the equation in exponential form, set the exponents equal to each other and solve.
c. Use the fact that the logs have the same base to add the expressions on the right side of the equation together. Express the results in exponential form, set the exponents equal to each other and solve.
d. Use the fact that since both sides of the equations have logarithms with the same base to set the expressions equal to each other and solve.
asked 2022-02-05
ax=b12, by=c13, cz=a12
What is the value of xyz?
asked 2022-02-02

How do you simplify the expression: ?9x+4y7x+2y?

asked 2020-11-26
Two spelunkers (cave explorers) were exploring different branches of an underground cavern. The first was able to descend 198 ft farther than twice the second. If the first spelunker descended a 1218 ft, how far was the second spelunker able to descend?
asked 2021-11-12
To calculate: The partial decomposition of 2x3x2+8x16x4+5x2+4.
asked 2021-11-19
To calculate: The solution set of the polynomial equation
11v2+23v1+2=0
asked 2021-10-03
To calculate: Thesolution of compound inequality
24x36,
if possible then write theanswer in interval notation.